2007
DOI: 10.1099/mic.0.2007/006080-0
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of two K+ transporters of Debaryomyces hansenii

Abstract: Two genes from the halotolerant yeast Debaryomyces hansenii were cloned, DhTRK1 and DhHAK1. These genes encode K + transporters with sequence similarities to the TRK and HAK transporters from Debaryomyces occidentalis and Candida albicans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
29
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 56 publications
(71 reference statements)
2
29
0
1
Order By: Relevance
“…Both S. occidentalis and D. hansenii possess a HAK-type transporter as well [42,90]. For S. occidentalis, it has been proposed that SoTrk1 plays an important role in the control of the membrane potential and mediates K ?…”
Section: Trk Transporters In S Cerevisiaementioning
confidence: 99%
See 1 more Smart Citation
“…Both S. occidentalis and D. hansenii possess a HAK-type transporter as well [42,90]. For S. occidentalis, it has been proposed that SoTrk1 plays an important role in the control of the membrane potential and mediates K ?…”
Section: Trk Transporters In S Cerevisiaementioning
confidence: 99%
“…For D. hansenii, which lives in marine habitats and thus in presence of K ? concentrations in the mM range, both DhTrk1 and DhHAK have been suggested to behave as low-affinity transporters [90].…”
Section: Trk Transporters In S Cerevisiaementioning
confidence: 99%
“…Subsequently, HAK1-orthologous genes have been found in many other organisms, such as the nonconventional yeasts D. hansenii (220) and Hansenula polymorpha (J. M. Siverio, personal communication), the micelial fungus N. crassa (104), the moss Physcomitrella patens (84), and higher plants (259,276 ϩ ions, is quantitatively conserved between C. albicans and S. cerevisiae. However, the secondary function, chloride efflux channeling, is present but poorly conserved between the two species, being highly variant with respect to activation velocity, amplitude, flickering (channel-like) behavior, pH dependence, and inhibitor sensitivity (170).…”
mentioning
confidence: 99%
“…However, an interesting approach was followed by Prista and coworkers (221), who showed that transformation with genes from D. hansenii can improve the salt tolerance of a wild-type S. cerevisiae strain. Concerning K ϩ transporters, the most important novelty compared to the situation in S. cerevisiae or S. pombe is the existence of a single TRK gene and an additional and completely different transporter encoded by D. hansenii HAK1 (DhHAK1) (220).…”
mentioning
confidence: 99%
“…También se han encontrado transportadores del tipo TRK en Neurospora crassa (Haro et al, 1999), Schwanniomyces occidentalis (Banuelos et al, 2000) y Debaryomyces hansenii (Prista et al, 2007). En estas especies, además de los sistemas de transporte del tipo TRK, también están presentes otro tipo de transportadores de potasio, los HAK (HighAffinity K + -transporter), que no existen en S. cerevisiae.…”
Section: El Transporte De Potasio En Saccharomyces Cerevisiaeunclassified